Atypical Face Processing in Children With Tuberous Sclerosis Complex. (December 2013) - Jeste, Shafali Spurling; Hirsch, Suzanna; Vogel-Farley, Vanessa; Norona, Amanda; Navalta, Mary-Clare; Gregas, Matt C.; Prabhu, Sanjay P.; Sahin, Mustafa; Nelson, Charles A.
There is a high incidence of autism in tuberous sclerosis complex. Given the evidence of impaired face processing in autism, the authors sought to investigate electrophysiological markers of face processing in children with tuberous sclerosis complex. The authors studied 19 children with tuberous sclerosis complex under age 4, and 20 age-matched controls, using a familiar–unfamiliar faces paradigm. Of the children, 6 with tuberous sclerosis complex (32%) had autism. Children with tuberous sclerosis complex showed a longer N290 latency than controls (276 ms vs 259 ms, P = .05) and also failed to show the expected hemispheric differences in face processing. The longest N290 latency was seen in (1) children with autism and tuberous sclerosis complex and (2) children with temporal lobe tubers. This study is the first to quantify atypical face processing in children with tuberous sclerosis complex. This functional impairment may provide insight into a mechanism underlying a pathway to autism in tuberous sclerosis complex.